Impact of qualified nursing management on Care Process - Caldeira, Angelita Giovana; Costa, Samuel Renoir Amaral; Sá, Vinicius Couto; Oliveira, Yanca dos Anjos (JRG Journal of Academic Studies, 2023)
Management is the act of administering or managing resources and/or people for some purpose, whether for their own benefit or that of a society. This article aims to discuss the impacts of qualified nursing management on the patient care process. Method: the study was carried out in the format of a Narrative Bibliographic Review, through the following steps: formulation of objectives, electronic search of publications associated with the theme, selection of data through inclusion and exclusion criteria, reading and interpretation and formulation of results for the critical interpretation of the findings. As inclusion criteria, original articles published between 2017 and 2023 were adopted and, for data analysis, those between 2018 and 2023 were considered, available in full in the selected databases: Scientific Electronic Library Online (SciELO), Google Scholar, Biblioteca Virtual Health (VHL); in Portuguese and that address the theme. Results: Nursing has been the most capable professional to perform management in the field of health, however this does not exempt the need for specialization, after all, for the execution of the care process with quality, managerial skills and abilities are paramount. Conclusion: Qualified nursing management plays a decisive role in the quality of the care process, not only for the patient but also for the quality of the team’s work, that is, a nurse, when carrying out his work with the quality and skills of a manager, tends to leverage the quality of service provided to the community, family, patient and professional team.